Assessing is not a joke. Alternative assessment practices in higher education. - Margherita Di Stasio; Maria Ranieri; Isabella Bruni (Firenze University Press, 2019)
In the context of a general renewal of teaching and learning practices in higher education, specific attention is paid to formative assessment and to the exploration of alternative assessment techniques. This paper presents a study carried out at the University of Florence involving around 200 first-year students in a course where such assessment techniques were adopted. The results showed mixed evidence. Regarding peer-assessment validity, statistical analysis gave a fair level of accordance. As for students' perception, their concerns about peer- and self-assessment emerged, especially because they understand assessment as a summative and not as a formative practice. Implications are discussed, paving the way for possible future research.   Valutare non è uno scherzo. Le pratiche alternative di valutazione nel contesto universitario. Nel quadro di un rinnovamento generale delle pratiche di insegnamento e apprendimento universitarie, un'attenzione particolare è rivolta alla valutazione in ottica formativa e all'esplorazione di tecniche di valutazione alternative. Questo articolo presenta uno studio condotto presso l'Università di Firenze che ha coinvolto circa 200 studenti del primo anno in un corso dove sono state utilizzate tali tecniche di valutazione. I risultati mostrano evidenze miste. L'analisi statistica ha fornito un giusto livello di accordo in merito alla validità della valutazione tra pari. Dalle percezioni degli studenti emergono invece resistenze verso la valutazione tra pari e l'autovalutazione, soprattutto perché gli studenti interpretano la valutazione come pratica sommativa e non come azione formativa. Le implicazioni di questi risultati vengono discusse nell'ottica di guidare possibili ricerche future.